DINAMIKA PEMERINTAHAN MUKIM DI ACEH BESAR PASCA KEMERDEKAAN INDONESIA (1946-2017) - Akmal Zakiyya; Zulfan ,; Alamsyah . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2019)
This study is entitled "The Dynamics of the Mukim Government in the Great Aceh Post Indonesian Independence (1946-2017)". Formulation of problems regarding how the position, duties, and functions of the mukim government in Aceh Besar, and how the public perception regarding the development of Mukim in Aceh Besar. This study aims to determine the position, duties and functions of the mukim government in Aceh Besar in the present, and to find out public perceptions about the development of mukim in Aceh Besar. The research uses historical (historical) methods, and uses a qualitative approach. Data obtained from the Library and Museum Prof. Ali Hasjmy, Aceh Information and Documentation Center (PDIA), Aceh Province Central Bureau of Statistics, and related agencies such as the Kuta Malaka Sub-District Office, Darul Kamal Sub-District Office and Lhoong Sub-District Office, as well as interviews with relevant figures in this study. The results of this study indicate that the mukim government in Greater Aceh began to change after Indonesian independence. This can be seen from the position, duties and functions of the mukim government. The position of mukim in Aceh Besar remains to this day, but the task has changed, all the needs of the community are addressed to the sub-district office, not directed to mukim, before the mukim was under the sultan but now the mukim is under the sub-district head. Whereas the community's view of the current position of the mukim has begun to be forgotten, there are even some people who do not know about the existence of mukim because everything has been transferred to the sub-district. So the role of mukim in the community begins to decrease. Even though the mukim government system in Aceh is one of the inheritance of the Aceh Darussalam Sultanate, its existence must be strengthened. Because it has a very important historical value for the people of Aceh in the future.